No Neon, but Jets in the Remarkable Recurrent Nova M31N 2008-12a?—Hubble Space Telescope Spectroscopy of the 2015 Eruption - Darnley, M. J. (2017)
The 2008 discovery of an eruption of M31N 2008-12a began a journey on which the true nature of this remarkable recurrent nova continues to be revealed. M31N 2008-12a contains a white dwarf (WD) close to the Chandrasekhar limit, accreting at a high rate from its companion, and undergoes thermonuclear eruptions that are observed yearly and may even be twice as frequent. In this paper, we report on Hubble Space Telescope Space Telescope Imaging Spectrograph ultraviolet spectroscopy taken within days of the predicted 2015 eruption, coupled with Keck spectroscopy of the 2013 eruption. Together, this spectroscopy permits the reddening to be constrained to E(B-V)=0.10+/- 0.03. The UV spectroscopy reveals evidence for highly ionized, structured, and high-velocity ejecta at early times. No evidence for neon is seen in these spectra, however, but it may be that little insight can be gained regarding the composition of the WD (CO versus ONe).